Unwrapping the European social model - Jepsen, Maria; Serrano Pascual, Amparo (Policy Press, 2006)
This book presents the outcome of a project coordinated by the European Trade Union Institute in which experts from different countries and social scientific disciplines (sociology, political science and economics) were invited to reflect on both the meaning and political status of the concept of the European Social Model (ESM).